Experimental validation of a trajectory tracking controller for a two-wheeled mobile robot - Kazed, Boualem; Guessoum, Abderrezak (IAES International Journal of Robotics and Automation (IJRA), 2026)
One of the most important and challenging problems of any kind of autonomous mobile robot is the ability to accurately control its onboard actuators, enabling it to fulfill a specified task. In the case of a two-wheeled mobile robot, this can only be achieved through a pair of adequate steering control signals. The main goal of this paper is to design a nonlinear multivariable controller allowing a self-made mobile robot prototype to track a prescribed trajectory. The basic principle of this control approach uses the Lyapunov theory as a primary tool to derive two steering control laws, making a three-state error vector converge to zero. Tuning the proposed controller parameters is carried out using an equivalent dynamic simulated model. This controller is then applied to generate the resulting command signals to the actual robot. This is achieved through a real-time high-speed serial communication between a stationary personal computer (PC), on which a MATLAB/Simulink version of this controller is performing, and an onboard Microchip 16 bits dsPIC33FJ64MC802 microcontroller running a firmware that takes care of all the data exchange with the connected PC and a set of two proportional integral derivative (PID) controllers ensuring that the rotational speeds of the robot wheels are kept very close to those required by the main controller, running on this PC. The performance of the proposed controller is evaluated using two different shaped trajectories. These tests show that the robot is able to gradually follow the required path with minimal lateral error. The robustness of this controller is demonstrated through its capability to reject external disturbances triggered during these experimental tests.